The perspectives of variable pay in Croatia is there a gap between employee pay preferences and actual compensation practices? - Načinović Braje, Ivana (2021)
Variable pay can have numerous benefits for the employee and the employer, however, the overall effect of variable pay will depend upon employee attitudes and preferences towards such form of compensation. Considering that reward systems in Croatia traditionally used the equality principle, the objective of this paper is to examine the role of variable pay from both employee and employer perspectives. Research results are based on a Delphi research of employee attitudes about variable pay and empirical investigation of actual employers" variable pay practices. The Delphi study results indicate a lack of consensus about employees" preferences for variable pay in Croatia. However, practice shows that some form of individual variable pay has been adopted by most examined companies. There is some gap between preferences for variable pay and actual compensation practices so this paper identifies conditions under which acceptance of variable pay can be improved.
Varijabilno nagrađivanje omogućava brojne prednosti za zaposlenike i poslodavce, međutim, krajnji učinak ovog sustava nagrađivanja ovisi o stavovima i preferencijama zaposlenika prema takvom načinu nagrađivanja. Uzimajući u obzir činjenicu da su se sustavi nagrađivanja u Hrvatskoj tradicionalno temeljili na principu jednakosti plaća, cilj ovog rada je istražiti ulogu varijabilnog nagrađivanja iz perspektive zaposlenika i poslodavaca. Provedeno je Delphi istraživanje o stavovima zaposlenika prema varijabilnom nagrađivanju te kvantitativno istraživanje praksi varijabilnog nagrađivanja. Nalazi Delphi istraživanja ukazuju na izostanak konsenzusa o preferencija zaposlenika u pogledu varijabilnog nagrađivanja u Hrvatskoj. Istraživanje praksi nagrađivanja u hrvatskim poduzećima pokazalo je da je neki oblik individualnog varijabilnog nagrađivanja primijenjen kod većine istraživanih poduzeća. Utvrđen je mogući jaz između preferencija zaposlenika prema varijabilnom nagrađivanju i stvarnih praksi nagrađivanja te se stoga u radu identificiraju preduvjeti za uspješnu primjenu varijabilnog nagrađivanja.
Bibliografija: 49 jed.
Summary ; Sažetak.
Keywords: Plaće -- Zaposlenici -- Nagrađivanje -- Varijabilno nagrađivanje; Hrvatska